ANALISIS HUKUM DARK POOLS SEBAGAI BENTUK TRANSAKSI EFEK DI LUAR BURSA SAHAM - Taufik Hidayat Lubis; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (Universitas Sumatera Utara, 2016)
ABSTRACT The development of information technology system is the one of investment increasing factor in a country and capital market has used it nowdays. At the same time, massive demand of market participants as the process of interaction with other market participants which aims to improve the interaction process hase been started in using slips and now scripless trading. The need of market participants with information technology systems development grows at the same time, it can be seen how in the 21st century has created a securities transactions known as dark pools. This method conducted off exchange considered one of the ways for investors to trade security in large numbers to get a lot of benefits such as pay off commission to the broker even be able to avoid the tax charge PPn and PPh.